Detection of Specific Polypeptide(s) Synthesized during the Sequential Stages of Differentiation in Dioscorea species - Kumar,Ashwani (2015)
ABSTRACTThe present investigation was aimed to detect the specific polypeptide(s) appeared during the sequential stages of differentiation. Among different explants, only nodal explants showed good results for callusing. Depending on the fresh and dry weight, best callus growth was observed on MS medium supplemented with NAA (2.5 mg/L) inDioscorea alata and 2, 4-D (2.0 mg/L) inD. deltoidea, respectively. This callus was used for the regeneration. Roots differentiation was observed on MS medium + NAA (2.0 mg/L) + IBA (0.5 mg/L) and shoots on MS medium + BAP (2.0 mg/L) + NAA (0.5 mg/L) in D. alata while in D. deltoidea, roots on RT medium + IAA (1.0 mg/L) and shoots on RT medium + BAP (1.0 mg/L) + NAA (0.5 mg/L). Continuous decrease was seen in the total soluble protein during the differentiation inD. alatawhereas inD. deltoidea, the protein content decreased upto initiation stage. Four root specific polypeptides (MW 25.56, 24.35, 19.13 and 18.2 kDa) and three shoot specific polypeptides (MW 53.7, 25.12 and 19.13 kDa) were synthesized during the differentiation inD. alata. Similarly, two root specific (MW 33.9 and 31.69 kDa) and one shoot specific (MW 16.98 kDa) polypeptide band were appeared during differentiation in D. deltoidea.